Age and creativity at work: The interplay between job resources, age and idea creativity - Niessen, Cornelia; Binnewies, Carmen; Ohly, Sandra (Journal of Managerial Psychology, 2008)
Purpose - The purspose of this study is to examine the interplay between job resources (job control and support for creativity from coworkers and supervisors), age and creativity at work. Job control and support for creativity are assumed to benefit idea creativity and to moderate the relationship between age and idea creativity. Design/methodology/approach - A sample of 117 nurses completed questionnaire measures and reported a creative idea they recently had at work. Three subject matter experts rated the creativity of the ideas. Hierarchical regression analyses were used to test hypotheses. Findings - Job control and support for creativity as well as age were unrelated to idea creativity. However, job control and support for creativity moderated the relationship between age and idea creativity. Age was positively related to idea creativity under high job control and negatively related to idea creativity under low job control and low support for creativity. Research limitations/implications - A potentially selective sample due to systematic drop-outs and a selection effect of older nurses might limit the generalizability of our results. Future research should examine the mechanisms that explain the moderating effect of job resources in the relationship between age and performance. Practical implications - Older employees' creativity at work can be raised by fostering support for creativity from coworkers and supervisors. Younger employees should get support to deal with a high level of job control, because their creativity is lowest under a high level of job control. Originality/value - Using data from multiple sources the study shows that different constellations of job resources benefit older and younger employees' creativity at work.
Keywords: Creative thinking; Nurses; Older workers; Resources